Representation of Pink and Green Symbols as Netizens' Resistance in the 17+8 Movement of People's Demands on Instagram - Ariza Qurrata A’yun; Aiska Safna Fitri (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
Instagram functions not only as a platform for information sharing but alsoas a digital public sphere that enables people to express aspirations andcollective resistance. This phenomenon is reflected in the 17+8 People'sDemands Movement, which was represented through the use of pink andgreen color symbols that later evolved into the Brave Pink and Hero Greentrends on Instagram. This study aims to analyze the representation of pinkand green symbols as forms of Indonesian netizens’ resistance within the17+8 People's Demands Movement. The novelty of this research lies in itsfocus on color symbols as a medium of digital resistance communication,whereas previous studies have predominantly examined resistancethrough textual narratives and hashtags. This research employs aqualitative descriptive approach using Roland Barthes’ semiotic analysis,which examines denotative, connotative, and mythical meanings. The datawere collected from Instagram posts containing pink and green symbolsrelated to the movement through observation, documentation, andliterature review. The findings reveal that, at the denotative level, the pinkand green symbols function as the visual identity of the movement. At theconnotative level, these symbols represent courage, solidarity, hope, andthe spirit of struggle in articulating socio-political demands. At themythical level, the symbols construct a narrative of public resistanceagainst social inequality through digital participation. The study alsodemonstrates that Instagram serves as a digital public sphere thatfacilitates the production, distribution, and exchange of meanings in aparticipatory manner, thereby strengthening collective awareness amongnetizens. This study concludes that visual symbols on social mediafunction as a medium of political communication and digital activism infostering collective resistance in the digital era.